Disparities in Breastfeeding and Use of Pasteurized Donor Human Milk. Issue 6 (November 2020) - Spatz, Diane L.
Abstract : Our breastfeeding expert, Dr. Spatz, advocates for using momentum from the Black Lives Matter campaign to elevate the critical role of human milk and breastfeeding for Black families. Per Dr. Spatz, while we can't change historical antecedents that have influenced breastfeeding among Black women, we could change the current paradigm to ensure that all families have equal access to evidence-based lactation information, care and support.